2020
DOI: 10.3390/ijerph17134781
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Maternal and Fetal Levels of Total Adiponectin, High Molecular Weight Adiponectin, Selected Somatomedins, and Birth Weight of Infants of Smoking and Non-Smoking Mothers

Abstract: The aim of the study was to determine the relationships between maternal smoking, total adiponectin, high molecular weight adiponectin (HMW adiponectin), selected somatomedins, and the birth weight of newborns. A total of 78 women with a healthy, singleton pregnancy, 41 active smokers and 37 non-smokers, and their offspring were studied. Total and HMW adiponectin, insulin-like growth factor I (IGF-I), and insulin-like growth factor binding protein-1 (IGFBP-1) and 2 (IGFBP-2) were determined in maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Several studies have shown that tobacco consumption during pregnancy directly affects the health of both mothers and neonates throughout the perinatal period [2][3][4][5][6][7][8][9]47,48]. Tobacco consumption during pregnancy can lead to epigenetic changes that affect the health of mothers and neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that tobacco consumption during pregnancy directly affects the health of both mothers and neonates throughout the perinatal period [2][3][4][5][6][7][8][9]47,48]. Tobacco consumption during pregnancy can lead to epigenetic changes that affect the health of mothers and neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found decreased cord blood IGF-1 levels in infants of mothers who smoked during pregnancy ( Table 3 ) [ 294 , 295 , 296 , 297 , 298 , 299 ]. Conversely, there were no associations with cord blood IGF-2, leptin, or c -peptide [ 294 , 295 , 297 , 298 ].…”
Section: Effects Of Maternal Disorders On Fetal Hormones Growth Facto...mentioning
confidence: 99%
“…Multiple studies have found decreased cord blood IGF-1 levels in infants of mothers who smoked during pregnancy ( Table 3 ) [ 294 , 295 , 296 , 297 , 298 , 299 ]. Conversely, there were no associations with cord blood IGF-2, leptin, or c -peptide [ 294 , 295 , 297 , 298 ]. Studies regarding the effect of maternal smoking on cord blood adiponectin levels have yielded variable results, with some reporting no differences [ 295 , 297 ] and another reporting lower values [ 298 ].…”
Section: Effects Of Maternal Disorders On Fetal Hormones Growth Facto...mentioning
confidence: 99%
See 1 more Smart Citation
“…Birth weight (BW) is considered a significant indicator for assessing fetal intrauterine growth, the nutritional condition and the health status of newborns, as well as predicting growth, developmental status, and health problems in adulthood [1][2][3]. In newborns with a normal weight, those with a low birth weight and macrosomia are related to higher morbidity and mortality [4][5][6], and low birth weight can result in poor mental development, risk of infection, and risk of developing cardiovascular disease later in life [7][8][9].…”
Section: Introductionmentioning
confidence: 99%